Anterior inferior plating versus superior plating for middle 1/3rd clavicle fracture: a prospective comparative study - Rudrappa, Girish H.; B. V., Deepak; Pradhaban, Gowthama (International Journal of Research in Orthopaedics, 2021)
Background: Fractures of the clavicle are common injuries that may result from direct blow or transmitted forces. Deformities are shortening and depression of lateral fragments. Various techniques are performed out of which superior and anteroinferior plating are widely used with each having its own merits and drawbacks. Our study compares the outcome between above mentioned techniques. Methods: We conducted a prospective comparative study of 60 patients who has met inclusion criteria and out of which 30 patients were treated with anteroinferior technique and 30 patients were treated with superior plating technique. Outcome measure were assessed through constant and murley score. Results: The demographic analysis of our study showed that the incidence of fracture is predominant among males (63.3%) with RTA being the most common mode of injury. AO/OTA classification which was used in our study revealed A1 as the most frequently involved group. Each group had 2 patients with infection post operatively which was managed with appropriate antibiotics. Increased incidence of delayed union was found in anterioinferior group (13.3%) with decreased hardware prominence in comparison with superior plating. Conclusions: There were no significant differences in functional outcome between both the groups except the fact that superior plating had higher chances of plate prominence. So either of the surgical technique can be employed depending upon the feasibility of surgeon.